Bentuk-Bentuk Kreativitas: ”Meningkatkan Kesejahteraan Mental Remaja Melalui Ekspresi Seni” - Salma, Nailis Syifa Nuris; Hasaniyah, Nur (Gayatri : Jurnal Pengabdian Seni dan Budaya, 2024)
This study aims to explore various forms of creativity in enhancing adolescent mental well-being through artistic expression. The introduction highlights the importance of mental well-being for adolescents and the role of art as an effective medium of expression. The research methodology employs a qualitative approach involving adolescent participants engaged in artistic activities such as painting, music, and theater. Data were collected through in-depth interviews and participatory observation. The results indicate that participation in artistic activities can enhance self-confidence, reduce stress, and strengthen social relationships among adolescents. The discussion elaborates on how the creative process in art allows adolescents to express emotions, cope with social pressures, and discover their identity. The conclusion of this study is that artistic expression can be an effective tool in improving adolescent mental well-being, providing them with a space to explore and express themselves in a positive manner.